2019
DOI: 10.3390/sym11030400
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Design Approach and Usability Evaluation of the Pain Management Mobile Applications

Abstract: The increasing popularity of mHealth is a promising opportunity for pain self-management. Mobile apps can be easily developed, but understanding the design and usability will result in apps that can retain more users. This research aims at identifying, analyzing, and synthesizing the current state-of-the-art of: (a) the design approach and (b) usability assessment of pain management mobile applications. A systematic literature review was conducted on 27 studies retrieved from Medline, PubMed, EMBASE, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…A robust existing scale, the Mobile App Rating Scale, also aims to assess the quality of the mobile apps [21]. A recent systematic review attempted to assess the quality of usability studies using a four-point scale [22] but failed to report on the process of development of the scale, or its reliability or validity, fundamental characteristics of any assessment or measurement instrument. Recently, a 15-items scale was developed to assess the methodological quality of usability studies for eHealth applications or general applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…A robust existing scale, the Mobile App Rating Scale, also aims to assess the quality of the mobile apps [21]. A recent systematic review attempted to assess the quality of usability studies using a four-point scale [22] but failed to report on the process of development of the scale, or its reliability or validity, fundamental characteristics of any assessment or measurement instrument. Recently, a 15-items scale was developed to assess the methodological quality of usability studies for eHealth applications or general applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…The types of mHealth mobile apps that have been shown to have common clinical value offer at least one of the following: supporting clinical diagnosis, promoting behavior change and increasing patient adherence with treatment plans, supporting self-management of a condition, or delivering disease-related education [8]. However, systematic and scoping reviews have found that most mHealth apps were developed for chronic pain rather than for acute pain management [9][10][11][12]. A recent scoping review focused on mHealth in the context of surgery found that out of 13 studies, only 5 focused on addressing postsurgery acute pain [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the pain management mHealth apps are designed without the involvement of health care providers [12] and older adults, resulting in apps that are ill-suited for an older audience [9,22]. Thus, there is a gap in the availability of innovative evidence-based mHealth tools and solutions to support older patients in the management of their acute pain once they leave the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they discuss the advantages and disadvantages of the included platforms. Shah and Chiew [ 32 ] analyze design and usability of mobile apps for pain management but not if and how users were involved in the development of these mobile tools. Vo et al [ 33 ] focus on the strengths and weaknesses of the use of mHealth apps, showing increased health care engagement and empowerment for patients actively using such apps.…”
Section: Introductionmentioning
confidence: 99%